Mercado de artes plásticas (sécs. XIX-XX) : relações de poder no trânsito produção/mediação/consumo - Supeleto, Natalie (2016)
This text sheds light on the consumption of art as of the modernist break period, the emergence of an independent market to the official recognition and the reorganization of the operating structures of the art field situated on the initial temporal and s